2021
DOI: 10.3389/fonc.2020.616094
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Treatable Hepatocellular Carcinoma Recurrence in Liver Recipients: A Nationwide Cohort Analysis

Abstract: BackgroundSurvival after post-transplant recurrence of HCC is dismal, and almost all treatments for recurrent HCC are off-labeled, without an extensive large-scale analysis. We aimed to delineate their post-recurrence courses and define benchmarks for comparing future treatment effectiveness.MethodsThree national databases, including health insurance, catastrophic illness, and the cause of death, were linked for cohort establishment and data collection during the period from 2005 to 2016. Patients with HCC rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…HCC recurrence occurs most frequently (60%) in the first 2 years post-transplant [ 12 , 33 , 37 ], and this early recurrence is predictive of worse prognosis, often with the increased disease burden and extrahepatic metastases [ 17 , 19 , 38 ], One recent study by Kim et al [ 35 ], demonstrated median timing of recurrence for single intrahepatic (20.6 months; interquartile range [IQR], 9.8–32.1), multiple intrahepatic (9.6 months; IQR, 5.2–14.4), single extrahepatic (11.1 months; IQR, 4.6–19.0), and single lung recurrence (21.4 months; IQR, 10.4–41.1). Late recurrence (beyond 2 years) have also been reported and may have more favorable tumour biology, with better response to locoregional treatments [ 33 , 39 ].…”
Section: Post-transplant Surveillance For Hcc Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…HCC recurrence occurs most frequently (60%) in the first 2 years post-transplant [ 12 , 33 , 37 ], and this early recurrence is predictive of worse prognosis, often with the increased disease burden and extrahepatic metastases [ 17 , 19 , 38 ], One recent study by Kim et al [ 35 ], demonstrated median timing of recurrence for single intrahepatic (20.6 months; interquartile range [IQR], 9.8–32.1), multiple intrahepatic (9.6 months; IQR, 5.2–14.4), single extrahepatic (11.1 months; IQR, 4.6–19.0), and single lung recurrence (21.4 months; IQR, 10.4–41.1). Late recurrence (beyond 2 years) have also been reported and may have more favorable tumour biology, with better response to locoregional treatments [ 33 , 39 ].…”
Section: Post-transplant Surveillance For Hcc Recurrencementioning
confidence: 99%
“…Late recurrence (beyond 2 years) have also been reported and may have more favorable tumour biology, with better response to locoregional treatments [ 33 , 39 ]. Given the greater proportion of early recurrences and the observed worse prognosis, current data supports intense surveillance for the first 2 years post-transplant, to identify early recurrences [ 29 , 33 , 37 ].…”
Section: Post-transplant Surveillance For Hcc Recurrencementioning
confidence: 99%
“…Studies have shown that the average survival time until recurrence is diagnosed ranges between 10.1 and 12.4 months [ 7 , 28 , 121 122 ] and depends on various factors. Based on these factors, several scales of risk of death for patients diagnosed with recurrence have been created.…”
Section: Surveillance Treatment Of Recurrencementioning
confidence: 99%
“…The average survival in the low-risk, average-risk, and high-risk groups were 70.6, 12.2, and 3.4 months, respectively [ 120 ]. Other authors also reported poor prognosis for patients with early recurrence [ 122 ] and not qualifying for radical treatment, while 1-year and 2-year survival after radical recurrence resection was 93.8% and 52.6%, respectively [ 127 ]. Some authors indicate the benefits of immunosuppression conversion to sirolimus in patients who are not treated surgically [ 121 , 127 , 128 ].…”
Section: Surveillance Treatment Of Recurrencementioning
confidence: 99%
“…As the expansion of eligible criteria to liver transplantation for HCC, the outcomes of liver transplantation for primary, recurrent, or down-staged HCCs might be different. Downstaging of HCC to reduce post liver transplant recurrence is another hotspot for investigation [ Bhatti et al , ( 5 )]. Bhatti et al reported their data that LDLT without prior downstaging could reach comparable survival for T2-T4a HCC with lower AFP.…”
mentioning
confidence: 99%